Neuropathic MORC2 mutations perturb GHKL ATPase dimerization dynamics and epigenetic silencing by multiple structural mechanisms - Christopher H. Douse (Nature Portfolio, 2018)
Microrchidia CW-type zinc finger protein 2 (MORC2) is an effector of epigenetic silencing by the human silencing hub (HUSH). Here the authors present the crystal structures of MORC2 and disease-causing MORC2 mutants and give mechanistic insights into how MORC2 mediates HUSH-dependent silencing.